2018
DOI: 10.1111/rda.13144
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of miRNAs in neonatal cloned bovines with collapsed lungs and respiratory distress

Abstract: Neonatal respiratory distress is a major mortality factor in cloned animals; however, the pathogenesis of this disease has rarely been investigated. Previous studies have shown that miRNAs regulate critical genes related to lung development, cell differentiation, surfactant synthesis, secretion and lung disease. This study aimed to examine differentially expressed miRNAs in collapsed lungs of cloned bovine neonates and normal lungs in order to identify key pathways and functions that might be related to the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Children with ARDS with a high expression of miR‐92 and miR‐122 have a poor prognosis and a higher risk of death. It has been suggested that serum miRNA expression level is significantly increased in children with ARDS, which is closely related to the severity and prognosis of ARDS in children 21 . To further explore the prognostic value of miR‐92 and miR‐122 in children with ARDS, ROC curve analysis was performed showing that the optimal cut‐off values of serum miR‐92 and miR‐122 expression and LUS score to predict the death of ARDS children were 2.93, 0.21, and 16.30 points, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Children with ARDS with a high expression of miR‐92 and miR‐122 have a poor prognosis and a higher risk of death. It has been suggested that serum miRNA expression level is significantly increased in children with ARDS, which is closely related to the severity and prognosis of ARDS in children 21 . To further explore the prognostic value of miR‐92 and miR‐122 in children with ARDS, ROC curve analysis was performed showing that the optimal cut‐off values of serum miR‐92 and miR‐122 expression and LUS score to predict the death of ARDS children were 2.93, 0.21, and 16.30 points, respectively.…”
Section: Discussionmentioning
confidence: 99%